Avaliação da cor e sensibilidade dolorosa durante clareamento dental caseiro associado a dessensibilizantes tópicos - Oliveira, Diogo Alexander de (2014)
Toothpastes containing desensitizing agents (DES) have been introduced in the market in order to minimize the dentin hypersensitivity. The aim of this study was to compare the action of different DES reported on dentin sensitivity and the color change when associated with at-home bleaching using 10% carbamide peroxide. Sixty volunteers were randomly divided into four groups (n = 15): GD desensitizing gel containing 5% potassium nitrate and 2% sodium fluoride, D1 desensitizing dentifrice with 8% arginine and 1.10% sodium monofluorophosphate; D2 - desensitizing dentifrice with 5% sodium calcium phosphosilicate and 1.10% sodium monofluorophosphate; PL placebo (control). Nightguard vital bleaching with 10% carbamide peroxide was performed during 4 weeks. Color data were measured using a digital spectrophotometer Vita Easyshade and color scale Vita Bleachedguide 3D -Master and submitted to ANOVA and Tukey and Kappa (5 %), showing no difference between groups for the color parameter of the teeth in any of the reviews. Data sensitivity were grouped in scores and submitted to Kruskal-Wallis test (5%), it has been possible to conclude that the use of DES is able to reduce the intensity of tooth sensitivity during bleaching